Phylogenetic relationships and generic realignments in the early diverging subtribe Pentziinae (Asteraceae, Anthemideae). (12th June 2015) - Magee, Anthony R.; Nicolas, Antoine N.; Tilney, Patricia M.; Plunkett, Gregory M.
<x xml:space="preserve">Abstract</x> Pentziinae are a subtribe of tribe Anthemideae (Asteraceae), comprising seven almost exclusively southern African endemic genera and c. 60 species. Generic delimitations and relationships in the subtribe are explored using parsimony and Bayesian analyses of nuclear (internal transcribed spacer, ITS) and plastid (ndhF, psbA‐trnH, trnK‐rps16 and rpl32‐trnL) DNA regions, with morphological and fruit anatomical studies. Phylogenetic analyses for 72 accessions (43 species) representing 72% of the subtribe indicate that several of the genera are not monophyletic as currently circumscribed. Pentzia tortuosa differs from its congeners in its inconspicuously three‐ribbed fruits and in several other distinctive morphological characters. In the phylogenetic trees based on the nuclear dataset, P. tortuosa is recovered in the perennial clade with its congeners, but in the plastid data set, it is strongly placed among the early diverging lineages comprising annual taxa with three‐ribbed fruits. Even with the exclusion of P. tortuosa, Pentzia remains paraphyletic by the inclusion of at least Rennera and possibly also Cymbopappus and Marasmodes. A possible sister relationship between Marasmodes and Pentzia, however, cannot be excluded. The four Rennera specise are therefore here transferred to Pentzia, whereas Marasmodes and Cymbopappus are retained pending further investigation. Among the annual lineages, Foveolina is also found to be polyphyletic, with F. dichotoma (the type species) and F. tenella clearly allied with Oncosiphon, and the anomolous species, F. burchellii, recovered with Myxopappus in the nuclear trees. Both Myxopappus species share the disciform capitula and heteromorphic fruits with Foveolina burchellii (characters previously overlooked in Myxopappus and reported here for the first time). © 2015 The Linnean Society of London, Botanical Journal of the Linnean Society, 2015, 178, 633–647.